FRI0055 Histone deacetylase 1 (HDAC1): a novel therapeutic target in rheumatoid arthritis. (15th June 2017) - Göschl, L; Bonelli, M; Saferding, V; Preglej, T; Seiser, C; Knapp, S; Backlund, J; Bock, C; Mathias, P; Hirahara, K; Scheinecker, C; Steiner, G; et al.
Abstract : Background: Autoreactive T cells have been shown to play a major role in Rheumatoid Arthritis, which drive the inflammatory process leading to an irreversible destruction of the joints. Gene transcription and regulation of proinflammatory cytokine production in T cells is regulated by epigenetic mechanisms. Histone deacetylases (HDACs) modify the epigenetic landscape by removing acetyl groups of lysine residues of histones, resulting in chromatin condensation and repression of transcription. The application of pan-HDAC inhibitors has been shown to be a potential therapeutic strategy. However, major side effects limited the clinical use and underline the need of more specific HDAC inhibitors. Objectives: Our aim was to to investigate whether HDAC1 is linked with the development of autoimmune diseases. Therefore we were using the collagen-induced arthritis model (CIA) and the experimental autoimmune encephalomyelitis model (EAE). Methods: Mice with a T cell specific deletion of HDAC1 (HDAC1cKO) were generated by using the CD4Cre/LoxP system. The clinical and the histological phenotype were assessed in the CIA and the EAE. Anti-collagen antibody levels were determined by ELISA. Qualitative and quantitative analysis of T cell subsets of the spleen and draining LN were assessed using flow cytometry. Additionally comparative RNA-sequencing of CD4 + T cells from wild type (WT) and HDAC1cKO mice was performed. Results: To address whether HDAC1 is involved in the pathogenesis of autoimmune diseases we induced the CIA and the EAE in WT and HDAC1cKO mice. Unexpectedly, HDAC1cKO mice did not develop any clinical or histological signs of inflammation, despite the presence of serum anti-CII antibodies. A similar protection against disease development was also observed in the context of EAE. A molecular analysis of HDAC1cKO CD4 + T cells revealed increased STAT1 phosphorylation in activated HDAC1cKO CD4 + T cells in comparison to WT cells. This was accompanied with an impaired expression of CCR6 in activated HDAC1cKO CD4 + T cells, which is an essential chemokine receptor for the development of arthritis and EAE. In line with this finding we observed increased expression of CCR6 in STAT1 -/- CD4 + T cells. This indicates a negative role of STAT1 in the regulation of CCR6 expression. Conclusions: Our data show the importance of HDAC1 as a key immune regulator in the pathogenesis of collagen induced arthritis. Therefore it might be considered as an interesting novel therapeutic target in RA. Disclosure of Interest: None declared